Positively Impacting Maternal Stress and Parental Adjustment through Community-Based Relationship Education (RE). Issue 3 (3rd April 2019) - Daire, Andrew P.; Liu, Xun; Tucker, Kelsee; Williams, Brooke; Broyles, Amanda; Wheeler, Naomi
ABSTRACT: Relationship education (RE) is a brief, strength-based psychoeducational intervention for couples that demonstrates strong outcomes to decrease individual and couple stress. The current study examined changes in relationship and family adjustment for expectant mothers following RE intervention. Participants included 91 pregnant women (64.8% racial or ethnic minorities) who participated in a community-based RE program. In examination of pre and post-intervention relationship assessment scale and parental stress and coping inventory results, RE intervention contributed to increased relationship satisfaction, and reduced parental distress, as well as to improved social support and family-based support scores among participants. In addition, relationship stress is a major contributor to stress during pregnancy that adds vulnerability for the health of low-income and ethnic minority expectant mothers and their children. Findings indicate the effectiveness of RE to significantly reduce stress for expectant mothers. Therefore, the use of RE as a low-cost and accessible intervention to combat stress provides positive implications for this vulnerable population.